PENINGKATAN KADAR BIOETANOL DARI KULIT NANAS DENGAN BEKAS CRACKING PERTAMINA RU III TERAKTIVASI SECARA KIMIA - Roni, Ki agus Ahmad; Rifdah, Rifdah; Susanto, Tri (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
Bioethanol is ethanol produced from glucose (sugar) fermentation, followed by the distillation process. Another method besides distillation is needed to increase the bioethanol produced. This study aims to increase the levels of bioethanol from pineapple skin using a cracking former catalyst by comparing the effectiveness of the use of chemically activated adsorbents using a base (NaOH) and acid (HCl). The adsorbent used in this study is the former RU III cracking catalyst, the FCC catalyst. The adsorbent is as a substitute for natural zeolite adsorbents, which are relatively expensive compared to the FCC catalyst. The results showed that the most effective ratio for bioethanol levels was 10 mL: 6 gr of adsorbent that activated by HCl, was 63.73%.